2001
DOI: 10.1034/j.1600-0714.2001.030008449.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) expression in oral tissues: possible relevance to angiogenesis, tumour progression and field cancerisation

Abstract: The aim of this study was to assess whether vascular endothelial growth factor (VEGF) expression in oral tissues is associated with angiogenesis, disease progression or field cancerisation. Vascularity and VEGF immunoreactivity were quantified in 68 archival specimens including normal oral mucosa (NOM), dysplasia (DYS) and squamous cell carcinoma (SCC). Vascularity increased significantly with disease progression; it was also higher in NOM adjacent to SCC than in NOM from healthy tissue, suggesting an associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 22 publications
(72 reference statements)
9
60
2
2
Order By: Relevance
“…Studies of oral pre-malignant tissue demonstrated a significant increase in MVD with progression from normal epithelium to invasive cancer (Carlile et al, 2001). In a large series of Barrett's oesophagus and associated adenocarcinoma, angiogenesis was markedly increased in pre-malignant lesions, which correlated with VEGF expression.…”
Section: Gastrointestinal Tractmentioning
confidence: 87%
“…Studies of oral pre-malignant tissue demonstrated a significant increase in MVD with progression from normal epithelium to invasive cancer (Carlile et al, 2001). In a large series of Barrett's oesophagus and associated adenocarcinoma, angiogenesis was markedly increased in pre-malignant lesions, which correlated with VEGF expression.…”
Section: Gastrointestinal Tractmentioning
confidence: 87%
“…15,16 VEGF is a 34-50-kD dimmer comprising 2 identical disulfide-linked subunits from differential splicing of a single gene. 9,17,18 VEGF is induced under hypoxic conditions in several tissue types and binds to tyrosine kinase receptors Fly-1 and KDR/ Flk-1 to stimulate angiogenic factors. 9,17,18 Those tissues that overexpress VEGF may be associated with portions of tumors that are biologically radioresistant and correlate with poor local control and overall survival.…”
mentioning
confidence: 99%
“…9,17,18 VEGF is induced under hypoxic conditions in several tissue types and binds to tyrosine kinase receptors Fly-1 and KDR/ Flk-1 to stimulate angiogenic factors. 9,17,18 Those tissues that overexpress VEGF may be associated with portions of tumors that are biologically radioresistant and correlate with poor local control and overall survival. In 2000, Smith et al reported VEGF expression as an independent risk factor for poor local and overall survival in head and neck squamous cell carcinoma (HNSCC).…”
mentioning
confidence: 99%
“…Activities of VEGF include enhancement of both angiogenesis and vascular permeability (9,10,12,14). VEGF is synthesized and secreted by many types of tumors, and expression levels of VEGF correlate with tumor status and prognosis (14,(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical staining for CD34 is used to evaluate microvessel density (MVD) in numerous tumor tissues, and intratumoral MVD is useful in predicting relapse or metastasis (22)(23)(24). The assessment of VEGF expression significantly correlates with MVD in different types of tumors (14,15,(17)(18)(19)25).…”
Section: Introductionmentioning
confidence: 99%